Using technology to accurately capture functional outcomes in sarcoma patients - Lu, Weiran (2013)
The project is in collaboration with the Nottingham University Hospital (NHS) and focuses on capturing information to inform the evaluation of the functional outcomes following sarcoma treatment. The Toronto Extremity Salvage Score (TESS) is the actual survey exist and already commonly used within the NHS for monitoring and evaluating the physical function of individuals and group of patients who undergoing limb preservation surgery for tumors of the extremities over time and measuring change in function due to different therapeutic interventions (1). • Problem: the existing process of paper-based TESS survey implementation in NHS failed to achieve their intended purpose of utilizes the functional outcomes data to capture the useful information for the further evaluation.